Foreign Travel Writers on Serbian Codifications - Drakić, Gordana; Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The article sheds light on the data on Serbian codes of law revealed by the travelers who visited the Principality of Serbia. The travel writers provide the information on the earliest attempts to codify law in Serbia and the contents of latterly enacted codes. The authors shall present the accounts of the travel writers and give the answer to what extent they correspond to the truth.